Efecto de la asociacion maiz-frijol sobre poblaciones de insectos plagas, con enfasis en Empoasca kraemeri Ross & Moore - Hernández R., J.C.; Vera Graziano, J; Schoonhoven, Aart van; Cardona Mejía, César (1984)
The effect of maize/bean intercropping on Empoasca kraemeri population and damage, populations of other phytophagous insects, the parasitic action of Anagrus sp. on E. kraemeri, ambient temp. and RH, light intensity, and bean leaf temp. was observed. Two planting dates and 3 maize densities in 2 bean var. were used. E. kraemeri population and damage decreased with increasing maize densities. Adult populations were larger when beans were planted simultaneously with maize. Large E. kraemeri adult populations were found in bean var. EMP-81 (tolerant) and large nymph populations in BAT-41 (susceptible); the damage was greater in the latter. Diabrotica spp. populations were larger with increasing maize densities. This was more evident when var. EMP-81 was planted 15 days after maize. No effect was detected of the different maize densities on Cerotoma sp. and Scaphytopius fuliginosus populations. The largest captures of these 2 species were in var. EMP-81. S. fuliginosus was more abundant in beans planted 15 days after maize. The percentage of parasitism by Anagrus sp. was higher in the association, whereas the percentage of unhatched E. kraemeri eggs was lower. Light intensity and temp. in bean leaf tissues decreased as maize densities increased. Leaf tissue temp. was higher in var. BAT-41. Bean yields were lower in the association, compared with the bean monocrop, possibly due to the competition for light with the maize crop. (AS)